Size effects on phonon localization and Raman enhancement in silicon nanotips. (13th November 2012) - Hofmann, Mario; Hsieh, Ya‐Ping; Liang, Chi‐Te; Chen, Yang‐Fang
<x xml:space="preserve">Abstract</x> Silicon nanotip arrays exhibit a wide variety of interesting optical and electronic properties associated with their dimensionality. We here investigate the effect of size‐induced changes on phonon localization and explain the enhanced Raman response. The occurrence of normally forbidden transitions in the photoluminescence spectra provides evidence for the predicted localization effect. Spatially resolved Raman spectroscopy reveals a continuous change of the silicon Raman peak position and peak width along the nanotip that is attributed to a smooth change between bulk properties at the base to size‐induced phonon confinement in the apex of the nanotip. This approach allows to exclude heating effects that normally overwhelm the phonon confinement signature. The Raman spectra are in excellent agreement with the spatial correlation model and the extracted correlation length is comparable to the tip dimensions. The observed phonon confinement coincides with an enhancement of the Raman scattering efficiency at the tip apex and results in a 40‐fold increase of the sample's Raman intensity compared with bulk silicon. These results provide a step toward the integration of Si based optoelectronic devices. Copyright © 2012 John Wiley & Sons, Ltd.